Psycho-Social Determinants of Ethnocentrism: A Study among Four Ethnic Groups in Ghana - lawson, victoria wendy; asumeng, maxwell; akotia, charity (Advances in Social Sciences Research Journal, 2014)
The study employed a descriptive correlational design in exploring psychological and social factors in a multi-ethnic community where ethnic prejudice is a probable root cause of conflict. Openness to experience and social dominance orientation were the psychological factors. The social factors were ethnic group membership and ethnic identification. A total of 240 respondents comprising Dagomba, Ga, Ewe and Akan ethnic groups were selected using quota and convenience sampling techniques. Questionnaire was used to collect data from the respondents. Findings from the standard multiple regression analysis of the data revealed that both psychological and social factors are significant determinants of ethnocentrism in a collectivist culture like Ghana. The result suggests that self-concept plays an essential role when discussing in-group favouritism.